Labelling GM‐free Products. A Case Study of Dairy Companies in Germany. (April 2016) - Punt, Maarten; Venus, Thomas; Wesseler, Justus
Summary: Food suppliers in the EU must comply with labelling regulations for genetically modified organisms (GMOs). However, excluded from mandatory labelling are food products derived from animals fed with GM feed (mainly GM soybean in the EU). Because of this labelling exemption, consumers are unable to identify which animal products were derived without the use of GMOs. Therefore, Germany and other countries introduced voluntary 'GM‐free' labelling legislations or guidelines that allow companies to signal that their products are 'GM‐free'. We present the results of a survey among German dairy companies. We asked them whether they produce 'GM‐free' and to assess the 'GM‐free' market in terms of (1) the current status, (2) potential benefits, (3) limitations and (4) risks. We find that smaller dairy companies mostly switch completely, whereas 'GM‐free' production of larger dairy companies is often limited. The results indicate that for switching to 'GM‐free' production, long‐term effects such as the creation of a positive image or differentiation from competitors are more important for dairy companies than short‐term effects such as higher sales or profit. Abstract : Food suppliers in the EU must comply with labelling regulations for genetically modified organisms (GMOs). However, excluded from mandatory labelling are food products derived from animals fed with GM feed (mainly GM soybean in the EU). Because of this labelling exemption, consumers are unable to identify which animal products were derived without the use of GMOs. Therefore, Germany and other countries introduced voluntary 'GM‐free' labelling legislations or guidelines that allow companies to signal that their products are 'GM‐free'.